LAW AND ORDER: FROM LITERARY RHETORIC TO JURIDICAL RHETORIC - Maria Luísa Malato (Revista Opinião Jurídica, 2020)
Objective: The analysis of the slogan “law and order” is related with the reading process of literary texts or cinematographic texts, applying them to the process of reading legal facts, highlighting the importance of the order of facts to the interpretation of facts.